Energy Contagion in the COVID-19 Crisis - Reinhold Heinlein; Gabriella Deborah Legrenzi; Scott M. R. Mahadeo (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We investigate the relationship between oil prices and stock markets of selected oil importers and oil exporters at the time of the COVID-19 pandemic. We provide evidence in favour of energy contagion, in term of significantly higher correlations between oil and stock markets returns during turbulent phases in the oil market, for all countries in our sample. Our results are robust to different crisis datings and consistent across different segments of the assets return distributions.
Keywords: C58; G01; G15; 330; contagion; intraday data; local correlation; oil; stock markets